Assessment and incorporation of in vitro correlates to pharmacokinetic outcomes in antibody developability workflows - Tushar Jain; Bianka Prinz; Alexander Marker; Alexander Michel; Katrin Reichel; Valerie Czepczor; Sylvie Klieber; Wei Sun; Sagar Kathuria; Sevim Oezguer Bruederle; Christian Lange; Lena Wahl; et al. (mAbs)
In vitro assessments for the prediction of pharmacokinetic (PK) behavior of biotherapeutics can help identify corresponding liabilities significantly earlier in the discovery timeline. This can minimize the need for extensive early in vivo PK characterization, thereby reducing animal usage and optimizing resources. In this study, we recommend bolstering classical developability workflows with in vitro measures correlated with PK. In agreement with current literature, in vitro measures assessing nonspecific interactions, self-interaction, and FcRn interaction are demonstrated to have the highest correlations to clearance in hFcRn Tg32 mice. Crucially, the dataset used in this study has broad sequence diversity and a range of physicochemical properties, adding robustness to our recommendations. Finally, we demonstrate a computational approach that combines multiple in vitro measurements with a multivariate regression model to improve the correlation to PK compared to any individual assessment. Our work demonstrates that a judicious choice of high throughput in vitro measurements and computational predictions enables the prioritization of candidate molecules with desired PK properties.